Pengaruh Perbedaan Diameter Lubang pada Tray Aerator Terhadap Penurunan Fe dan Mn pada Air Sumur dengan Media Karbon Aktif - Namira; Hidayah, Euis Nurul (Jurnal Serambi Engineering, 2025)
Polluted groundwater can be treated using tray aerator technology, particularly to reduce the concentration of iron (Fe) and manganese (Mn) in well water, especially in the Jombang area. This technology uses oxidation by introducing air through a tray aerator, which has variations in hole diameter and distance between trays. The study focused on the effect of variations in tray hole diameter (0.4 cm, 0.5 cm, 0.6 cm) and contact time on improving water quality. Activated carbon was also added as a medium to help adsorb pollutants. The results showed that tray aerators with the right diameter and spacing can significantly reduce Fe and Mn levels to meet drinking water quality standards according to government regulations. Parameters such as dissolved oxygen (DO), pH, temperature and Fe and Mn concentrations were measured periodically to evaluate the effectiveness of the aerator. This study is an important contribution to the development of more efficient and environmentally friendly water treatment technology.